EFEKTIFITAS PENGGUNAAN MODEL PEMBELAJARAN MEA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI MAS AL-AHLIYAH AEK BADAK - Desi Haryanti (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2018)
Abstract The aims of this study is to: 1) describe of using MEA learning model, 2) describe students’ mathematic problem solving ability before and after using MEA learning model, and 3) there is a significant influence of using MEA learning model on students’ mathematic problem solving ability at the eleventh grade students of MAS Al- Ahliyah Aek Badak. This research was conducted by applying experimental method (one group pretest post test design) with sample 29 students and they were taken by using simple total sampling technique. Observation and test were used in collecting the data. Based on descriptive analysis, it was found that: (a) the score of using MEA learning model was 3.2 (very good category), b) the average of students’ mathematic problem solving ability before using MEA learning model was 50.8 (fair category) and after using MEA learning model was 60.22 (very good category). Furthermore, by using paired sample ttest and helping SPSS version 17, the result showed the significant value was less than 0.05 (0.011<0.05). It means, there is a significant influence of using MEA learning model on students’ mathematic problem solving ability at the eleventh grade students of MAS Al- Ahliyah Aek Badak. Keywords: MEA learning model, mathematic problem solving ability